Productive Zakat Governance Model for Improving the Quality of Islamic Education - Ridwan, Muhamad; Salam, Abdus; Aspandi, Ade; Muttaqin, Muhammad Azhar (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine the model of productive zakat governance implemented by BAZNAS of Majalengka Regency, focusing on the implementation of zakat programs in the education sector, including scholarships, educational infrastructure development, and vocational training. It also explores the role of information technology in enhancing transparency and accountability in zakat distribution. The research employs a qualitative field-based approach by collecting primary data through direct observations, in-depth interviews with zakat management officials, beneficiaries, and educational institution administrators, as well as documentation of relevant institutional reports. Secondary data were obtained from internal publications, zakat distribution records, and program evaluations. The analysis of the collected data was conducted using the interactive model of Miles and Huberman, which involves data reduction, data display, and conclusion drawing to ensure systematic interpretation and validity of the findings. The findings reveal that BAZNAS Majalengka has successfully developed an effective digital-based zakat management system, which improves community participation and ensures targeted distribution. The zakat scholarship program has shown a positive impact on the social mobility and academic performance of students from underprivileged backgrounds. The study concludes that a transparent, collaborative, and technology-driven zakat governance model can serve as a strategic alternative funding source for the sustainable improvement of Islamic education quality at the local level.